Exploring general practitioner work in Upper Austria - Zelko, Erika (Zdravstveno varstvo, 2025)
Introduction: This study investigates the differences in patient care across various organisational forms of general practitioners (GPs) in Upper Austria. Methods: Data was collected from GPs across Upper Austria, examining patient demographics, prescription patterns, staff employment, services offered and the proximity of practices to hospitals. The variability in recording patient visit reasons was also analysed. Results: Of the 30 participating GPs (Response Rate 5.1%), 17 worked in single practices, 7 in group practices, and 6 in PHC units. In our sample, single practices tend to prescribe more medications for chronic conditions. Group practices and PHC centres are more prevalent in areas with larger populations, offer online appointment bookings more frequently and employ more staff. The study also highlights variability in documenting patient visit reasons, emphasising the need for standardised documentation practices. The most common reasons for the patient to contact their GP, based on ICPC-2 categories, were general and non-specific, respiratory and locomotor problems, and the most common chronic diseases seen in the practice are cardiovascular, endocrine diseases and locomotor system problems. The most common therapeutic procedures were counselling and prescription of medication. Conclusion: Our study, the first of its kind, reveals significant insights into the variability and adaptability of general medicine outpatient practices in Upper Austria, highlighting the need for improved diagnosis coding at the primary care level.
Keywords: general/family medicine; kodiranje; organisational type of practice; organizacijske oblike; primarna zdravstvena oskrba; primary healthcare; scope of activities; splošna/družinska medicina; storitve; Upper Austria; Zgornja Avstrija